Using the supporting material during the examination - Kudžma, Ričardas; Jakubonienė, Lina (Lietuvos matematikos rinkinys, 2011)
About twenty years ago all examinations at the Faculty of Mathematics of Vilnius University were oral. During the past years the situation has been changed radically – almost all examinations are writen. Written examinations can be open-book or closed-book. The older of autors of this article allows to prepare and to use during the mathematical analysis examinations the A4 sheet with specific information. The writen information can be from the knowledge level according to the Bloom’s taxonomy – definitions, formulations of theorems, formulae, but not solutions of problems, proofs of theorems. This sheet should be returned together with solutions of exams. The junior author investigated the preparation, usage and relation between the information in this A4 sheets with the results of exams in her Bachelor and Master theses.
Keywords: written examination; closed-book examination; open-book examination